The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.20546/ijcmas.2019.804.152
|View full text |Cite
|
Sign up to set email alerts
|

Character Association and Path Co-efficient Analysis in F2 Segregating Population of Cross “Arka Kamini x PG Violet” in China Aster (Callistephus chinensis [L.] Nees)

Abstract: during the year 2017-18 in the unreplicated design. The phenotypic correlation coefficients and path coefficient analysis were carried out for the F 2 segregating population of cross Arka Kamini × PG Violet in China aster for fifteen characters. The results revealed that flower yield per plant had high significant and positive correlation with the individual flower weight (0.599), flower diameter (0.562), disc diameter (0.491), number of flowers per plant (0.219) and number of branches per plant (0.197). Path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In line with the current finding [25], reported a positive and substantial link between tiller per plant and yield per plant, as well as a negative association between crude fiber content and yield in turmeric. Similarly [26,27], in fenugreek found that pod per plant and pod length had a positive connection with yield per plant. Likewise [28], found a substantial and positive relationship between the number of capsules per plant and the yield per plant.…”
Section: Correlation Of Yields With Other Traitsmentioning
confidence: 94%
“…In line with the current finding [25], reported a positive and substantial link between tiller per plant and yield per plant, as well as a negative association between crude fiber content and yield in turmeric. Similarly [26,27], in fenugreek found that pod per plant and pod length had a positive connection with yield per plant. Likewise [28], found a substantial and positive relationship between the number of capsules per plant and the yield per plant.…”
Section: Correlation Of Yields With Other Traitsmentioning
confidence: 94%